SAMARKAND – AN ANCIENT AND ALWAYS MAIDEN CITY - Abduhamidov Doniyorbek (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article provides information about the history of Samarkand, one of the ancient and young cities of our country, and its ancient architectural monuments.